Lymphocyte as a predictor of prognosis of COVID-19 patients: A hospital-based study - C. Biakhlupuii; Johan Vanlalpeka; Benjamin Lalrinpuia; Laltlanzovi; Ksh G. Devi; Lalrinawmi Hrahsel (Journal of Family Medicine and Primary Care, 2024)
Introduction: Lymphocytopenia has emerged as a simply obtained laboratory value that may correlate with prognosis. In this study we aim to study absolute Lymphocyte count after clinical recovery. Method and material: Observational study was conducted in Covid dedicated Hospital in Mizoram. Absolute lymphocyte count is obtained from the differential leucocyte count of the patients. The obsolute Lymphocyte count at the time of hospital admission is compared with the Absolute Lymphocyte count at the time of hospital discharge after the patient obtained clinical recovery. Result: Absolute Lymphocyte Count at the time of admission has a mean of 2004.48 and standard deviation of 1204.868. Absolute Lymphocyte Count at the time of discharge has a mean of 1943.68 and standard devaiton of 842.228. Pearsons correlation coefficientis showed that there is positive correlation between the variables (Correlation coeffiecient = .325). Also, the correlation is statistically significant (P < 0.05). Paired Sample t-test showed there is no statistical significant difference between Absolute Lymphocyte Count- at the time of admission and at the time of discharge (P > 0.05) at 95% Conficence Interval. Conclusion: Our study showed that Absolute Lymphocyte count had no signicant difference at the time of hospital admission and after clinical recovery.